(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2023)
Beach ridges with interspersed swales (BRIS), commonly referred to as BRIS soil or sandy soil, are extensively distributed along the eastern coast of Peninsular Malaysia. Despite the challenging nature of the lowland agricultural soil, characterised by its sandy texture and sterility, agricultural activities on BRIS soils have experienced an upward trend in recent times. The objective of this study was to conduct a literature review on the challenges and possibilities of roselle (Hibiscus sabdariffa L.) growth in the BRIS soil environment. Soil concerns can be classified into three categories: physical, chemical, and biological. The soil in BRIS is characterised by its acidic nature and low CEC values, with sand content occasionally reaching as high as 95 percent. Significant challenges associated with sandy soil conditions encompass soil water repellency (SWR), soil compaction, surface crust formation, soil erosion, low fertility, and Cation Exchange Capacity (CEC) value, as well as nutrient leaching into the groundwater, leading to pollution. The roselle plant is currently being commercially cultivated in the state of Terengganu as a substitute for tobacco in BRIS soil. This is due to the plant’s exceptional aeration and deep root zone. However, owing to its diminished fertility, its output is restricted. This book concentrates on the challenges related to BRIS soil and environmental concerns, including issues such as inadequate nutrient levels, weak soil structure, and excessive drainage. This review comprehensively elucidates the management strategies for sandy soil in the context of agricultural operations and evolving climatic conditions, thereby contributing to the advancement of research on the prospective cultivation of roselle.